How Can AI Help to Establish A Personal Learning Environment for K12 Students and How to Make It More Acceptable? - LIU, HUIQIAO (2020)
This dissertation is researched on how AI (Artificial Intelligence) can help to establish a PLE (Personal Learning Environment) for K12 (Kindergartens to 12 grade) students and how to make it more acceptable. The dissertation briefly explains the capabilities and the application of AI and introduced the theory of PLE and the application of AI in PLE for the education of K12 students. The Technology Acceptance Model and the Diffusion of Innovation Theory are employed in the dissertation to explain what factors should be noticed to increase the acceptance of the AI-supported PLE learning tools as a new learning method. The advantages and disadvantages of the existing AI-supported PLE applications are found, and the future development direction of AI-supported PLE tools are provided.